(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
The density and viscosity of Cu (II) soap urea complex derived from four edible oils (mustard, groundnut, sesame, soyabean) in non-aqueous solvents of varying composition has been determined at constant temperature. The results were used to determine the critical micelle concentration (CMC), soap-solvent interactions and the effect of chain length of the soap urea complex molecule on various parameters. The CMC values in higher volume % of methanol are higher those in higher volume % of benzene, with regards to chain length of the soap urea complex CMC value follow the order: CSoU>CSeU> CGU > CMU The conclusions with regard to soap- urea complex and soap- solvent interaction have been discussed in terms of well-known Masson’s and Jones- Dole equations. This vital information plays an important role in various industrial and biological applications.